An implicit 2-point block extended backward differentiation formula for integration of stiff initial value problems - Suleiman, Mohamed; Musa, Hamisu; Ismail, Fudziah (Institute for Mathematical Research, Universiti Putra Malaysia, 2015)
A class of implicit 2-point block extended backward differentiation formula (BEBDF) of order 4 is presented. The stability region of the method is constructed and shown to be A – stable. Results obtained are compared with an existing block backward differentiation formula (BBDF). The comparison shows that using constant step size and the same number of integration steps, our method achieves greater accuracy than the 2-point BBDF and is suitable for solving stiff initial value problems.